Dithiopheneindenofluorene (TIF) Semiconducting Polymers with Very High Mobility in Field‐Effect Transistors. Issue 36 (21st July 2017) - Chen, Hu; Hurhangee, Michael; Nikolka, Mark; Zhang, Weimin; Kirkus, Mindaugas; Neophytou, Marios; Cryer, Samuel J.; Harkin, David; Hayoz, Pascal; Abdi‐Jalebi, Mojtaba; McNeill, Christopher R.; Sirringhaus, Henning; et al.
Abstract : The charge‐carrier mobility of organic semiconducting polymers is known to be enhanced when the energetic disorder of the polymer is minimized. Fused, planar aromatic ring structures contribute to reducing the polymer conformational disorder, as demonstrated by polymers containing the indacenodithiophene (IDT ) repeat unit, which have both a low Urbach energy and a high mobility in thin‐film‐transistor (TFT) devices. Expanding on this design motif, copolymers containing the dithiopheneindenofluorene repeat unit are synthesized, which extends the fused aromatic structure with two additional phenyl rings, further rigidifying the polymer backbone. A range of copolymers are prepared and their electrical properties and thin‐film morphology evaluated, with the co ‐benzothiadiazole polymer having a twofold increase in hole mobility when compared to theIDT analog, reaching values of almost 3 cm 2 V −1 s −1 in bottom‐gate top‐contact organic field‐effect transistors. Abstract : A novel bridged donor (TIF) with a large planar aromatic core is designed and synthesized using a novel intramolecular CH activation strategy. ThisTIF unit is copolymerized withBT, FBT, DFBT, andTT repeat units, with theTIF‐BT copolymer exhibiting a higher p‐type mobility (2.8 cm 2 V −1 s −1 ) compared to previously reportedIDT‐BT andIDTT‐BT copolymers using the same device‐fabrication method.